Validation of new combinations in the fungal genera Cancellidium, Mycoenterolobium (Ascomycota) and Juncorrhiza (Entorrhizomycota) - Worobiec, Grzegorz; Piątek, Marcin; Riess, Kai; Lutz, Matthias; Worobiec, Elżbieta (Phytotaxa, 2026)
N/A